A microfluidic system for dynamic yeast cell imaging - Philip J. Lee; Noah C. Helman; Wendell A. Lim; Paul J. Hung (BioTechniques)
The investigation of cellular processes and gene regulatory networks within living cells requires the development of improved technology for dynamic, single cell imaging. Here, we demonstrate a microfluidic system capable of mechanical trapping of yeast cells with continuous flow and flow switching capability during time-lapse high magnification fluorescence imaging. The novel functionality of the system was validated by observing the response of pheromone-induced expression of GFP in Saccharomyces cerevisiae.